2022
DOI: 10.1088/1361-648x/ac9e84
|View full text |Cite
|
Sign up to set email alerts
|

Landau levels and snake states of pseudo-spin-1 Dirac-like electrons in gapped Lieb lattices

Abstract: This work reports the three-band structure associated with a Lieb lattice with arbitrary nearest and next-nearest neighbors hopping interactions. For specific configurations, the system admits a flat band located between two dispersion bands. Three inequivalent Dirac valleys are identified so that the quasi-particles are effectively described by the spin-1 Dirac-type equation. Under external homogeneous magnetic fields, the Landau levels are exactly determined as the third-order polynomial equation for the ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…2b for illustration. A similar analysis holds for higher values of t 3 , where the Dirac points are displaced with respect to K. For a detailed discussion, see [13].…”
Section: Lieb Lattice and Pseudospin-1 Dirac Equationmentioning
confidence: 54%
See 2 more Smart Citations
“…2b for illustration. A similar analysis holds for higher values of t 3 , where the Dirac points are displaced with respect to K. For a detailed discussion, see [13].…”
Section: Lieb Lattice and Pseudospin-1 Dirac Equationmentioning
confidence: 54%
“…Their geometries can extend beyond the honeycomb lattice. For instance, there are Kagome [10], Dice or α − T 3 [11,12], and Lieb lattices [13,14], which lead to effective pseudospin-1 Dirac equations. It was recently showed that the Kagome lattice can be obtained from a geometrical deformation of the Lieb lattice [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This set, shown in figure 2, consists of the two intersecting planes A and B, which are defined by equations ( 14) and (16). The energy of the upper and lower dispersion bands on these planes are described by solutions (19) and (21). The corresponding eigenfunctions are given through the general formula (10).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the existence of infinite series of bound states near the flat band appears to be of great interest [18]. Very recently, the transport properties and snake states of pseudospin-1 Diraclike electrons have been analyzed by Jakubský and Zelaya [20,21] in Lieb lattice under barrierand well-like electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%